Serum tryptase, interleukin 6 and SCORMA Index as disease severity parameters in childhood mastocytosis - Lange, Magdalena; Renke, Joanna; Gleń, Jolanta; Niedoszytko, Marek; Nedoszytko, Bogusław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Introduction : Mastocytosis is a rare, heterogeneous disease that is characterized by an increased number of mast cells in one or more organs. In children cutaneous mastocytosis (CM) is the predominant clinical presentation of the disease, although systemic involvement also may occur. Mastocytosis was classified according to World Health Organization (WHO) criteria; the extent and the intensity of symptoms were assessed clinically using a scoring system (Scoring Mastocytosis Index, SCORMA). Aim: To estimate the diagnostic and prognostic value of the SCORMA Index, serum tryptase and interleukin-6 (IL-6) level in childhood-onset mastocytosis. Material and methods : In a total of 65 children aged 3 months-17 years mastocytosis was diagnosed according to WHO guidelines. In all of them SCORMA Index, serum tryptase and IL-6 were determined. These parameters were compared with clinical forms of mastocytosis and the intensity of clinical symptoms to investigate correlations between them. Results: Cutaneous mastocytosis was diagnosed in 64 children (58 cases of MPCM, 6 cases of DCM). Systemic mastocytosis (SM) with bone marrow involvement was recognized in 1 child. In children with diffuse CM (DCM) the levels of serum tryptase, IL-6 and SCORMA Index were higher compared with maculopapular CM (MPCM). The most intensive mast cell related symptoms were found in DCM. There was a positive correlation of SCORMA Index with tryptase and IL-6 level, indicating the value of these parameters in the assessment of mastocytosis. A statistically significant increase of plasma IL-6 levels was found in children with osteoporosis/osteopenia (n = 7) when compared to children without osteoporosis/osteopenia (n = 58). Conclusions : SCORMA Index is a useful clinical tool for evaluating the extent and intensity of cutaneous symptoms. Tryptase is a surrogate marker of severity of both CM and SM. High and increasing serum tryptase level signify disease progression. Our observations suggest that increased plasma IL-6 helps to identify patients with a risk of systemic involvement. However, further studies on larger populations should be performed to determine the practical value of this cytokine.